PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION - Mediawati, Mediawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
IPS Learning is focused on the teacher as the primary source of learning, then a lecture to choice in learning, so students get bored and think of learning IPS unattractive and consequently, the value of students is low. This study aimed to describe the learning outcomes of students in learning by using the IPS model of cooperative learning GI type. Student learning outcomes cycles 1 and 2 meetings I average 53.0 and 68.6. Cycle II meetings 1 and 2 the average value of 82.0 and 82.3. The study uses a model of GI, can improve student learning outcomes in social studies learning. Keywords: Group Investigation Model, Student Results